LA MOTIVATION DES ACTES DE L’ADMINISTRATION PUBLIQUE/THE RATIONALE BEHIND THE ACTS OF A PUBLIC ADMINISTRATION - Bolduc, Roch (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF